Manajemen Kearsipan Berbasis Digital Sistem Informasi Mumtaz ( Si Mumtaz ) Di Madrasah Aliyah Zainul Hasan 1 Genggong - Indi Wardah; Ismatul Izzah; Poppy Rachman (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2024)
This research aims to analyze the digital-based archives management of the Mumtaz Information System at Madrasah Aliyah Zainul Hasan 1 Genggong which can realize the quality of records management in administrative services effectively and efficiently at Madrasah Aliyah Zainul Hasan 1 Genggong. This research uses descriptive qualitative methods. The data collection instruments used were interviews, observation and documentation. The research results obtained show that the digital-based archive management of the Mumtaz information system at Madrasah Aliyah Zainul Hasan 1 Genggong through the planning, management, control and supervision stages has been managed effectively and efficiently, however digital archive management has limited storage for many archives. Digital archive management activities include at least two things, namely: archive storage and archive retrieval. Digital archive storage activities are archive management activities that start from transfer of archive media to the arrangement of archives in new media. The use of digital archives already uses the official application from Madrasah Aliyah Zainul Hasan 1 Genggong, for this reason, in realizing the quality of administration of administrative services effectively and efficiently at Madrasah Aliyah Zainul Hasan 1 Genggong, the official application is used, namely the Mumtaz Information System (SI MUMTAZ) in managing archives digitally. Keywords: Archives Management; Digital and Si Mumtaz.